2008
DOI: 10.1002/cbic.200800104
|View full text |Cite
|
Sign up to set email alerts
|

Benzene Polyphosphates as Tools for Cell Signalling: Inhibition of Inositol 1,4,5‐Trisphosphate 5‐Phosphatase and Interaction with the PH Domain of Protein Kinase Bα

Abstract: Novel benzene polyphosphates were synthesised as inositol polyphosphate mimics and evaluated against type-I inositol 1,4,5-trisphosphate 5-phosphatase, which only binds soluble inositol polyphosphates, and against the PH domain of protein kinase Balpha (PKBalpha), which can bind both soluble inositol polyphosphates and inositol phospholipids. The most potent trisphosphate 5-phosphatase inhibitor is benzene 1,2,4-trisphosphate (2, IC(50) of 14 microM), a potential mimic of D-myo-inositol 1,4,5-trisphosphate, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
(120 reference statements)
0
13
0
1
Order By: Relevance
“…[245] Recent data have also focussed upon receptor subtypes in concert with adenophostin analogues. [246] Designing simple synthetic modulators of the Ins(1,4,5)P 3 receptor not based upon inositol that would mimic a myoinositol polyphosphate has always been achallenge.Since the publication of the first antagonist lead, biphenyl 2,3',4,5',6pentakisphosphate BiPh(2,3',4,5',6)P 5 ,( 262;F igure 15), [247] which also exhibits other biological activities, [248] similar compounds have been reported that explore the growing potential of benzene polyphosphates in cell-signaling applications.T hus,anoncarbohydrate/inositol phosphate Ins-(1,4,5)P 3 receptor agonist, based upon ab iphenyl structure and decorated with phosphate groups-biphenyl 3,3',4,4',5,5'hexakisphosphate (BiPh(3,3',4,4',5,5')P 6 , 263)-has been syn-…”
Section: Biphenyl Phosphate Derivativesmentioning
confidence: 99%
“…[245] Recent data have also focussed upon receptor subtypes in concert with adenophostin analogues. [246] Designing simple synthetic modulators of the Ins(1,4,5)P 3 receptor not based upon inositol that would mimic a myoinositol polyphosphate has always been achallenge.Since the publication of the first antagonist lead, biphenyl 2,3',4,5',6pentakisphosphate BiPh(2,3',4,5',6)P 5 ,( 262;F igure 15), [247] which also exhibits other biological activities, [248] similar compounds have been reported that explore the growing potential of benzene polyphosphates in cell-signaling applications.T hus,anoncarbohydrate/inositol phosphate Ins-(1,4,5)P 3 receptor agonist, based upon ab iphenyl structure and decorated with phosphate groups-biphenyl 3,3',4,4',5,5'hexakisphosphate (BiPh(3,3',4,4',5,5')P 6 , 263)-has been syn-…”
Section: Biphenyl Phosphate Derivativesmentioning
confidence: 99%
“…To clarify which structural properties of BiPh(2,3′,4,5′,6)P 5 might favor its interaction with SHIP2, we compared its potency with the simpler benzene 1,2,3-trisphosphate (Bz(1,2,3)P 3 ) and benzene 1,2,4,5-tetrakisphosphate (Bz(1,2,4,5)P 4 ) 16 (Figure 1 panel A). Enzyme activity was assayed by measuring inorganic phosphate released from the substrate Ins(1,3,4,5)P 4 (100 μM) using the malachite green phosphate assay (BioAssay Systems).…”
mentioning
confidence: 99%
“…[246] There has always been the challenge to design simple synthetic modulators of the Ins(1,4,5)P 3 receptor not based upon inositol that would mimic a myo-inositol polyphosphate. Since the publication of the first antagonist lead, biphenyl 2,3′,4,5′,6-pentakisphosphate BiPh(2,3′,4,5′,6)P 5 , (262 in Figure 15), [247] which also exhibits other biological activities, [248] …”
Section: Biphenyl Phosphate Derivativesmentioning
confidence: 99%
“…Designing simple synthetic modulators of the Ins(1,4,5)P 3 receptor not based upon inositol that would mimic a myo ‐inositol polyphosphate has always been a challenge. Since the publication of the first antagonist lead, biphenyl 2,3′,4,5′,6‐pentakisphosphate BiPh(2,3′,4,5′,6)P 5 , ( 262 ; Figure ), which also exhibits other biological activities, similar compounds have been reported that explore the growing potential of benzene polyphosphates in cell‐signaling applications. Thus, a noncarbohydrate/inositol phosphate Ins(1,4,5)P 3 receptor agonist, based upon a biphenyl structure and decorated with phosphate groups—biphenyl 3,3′,4,4′,5,5′‐hexakisphosphate (BiPh(3,3′,4,4′,5,5′)P 6 , 263 )—has been synthesized that surprisingly stimulates the release of Ca 2+ ions .…”
Section: Myo‐inositolmentioning
confidence: 99%